A randomized placebo-controlled trial of desipramine, cognitive behavioral therapy, and active placebo therapy for low back pain. Issue 6 (June 2020) - Gould, Hilary M.; Atkinson, Joseph Hampton; Chircop-Rollick, Tatiana; D'Andrea, John; Garfin, Steven; Patel, Shetal M.; Funk, Stephen D.; Capparelli, Edmund V.; Penzien, Donald B.; Wallace, Mark; Weickgenanta, Anne L.; Slater, Mark; et al.
Abstract : Abstract: This clinical trial evaluated the independent and combined effects of a tricyclic antidepressant (desipramine) and cognitive behavioral therapy (CBT) for chronic back pain relative to an active placebo treatment. Participants (n = 142) were patients experiencing daily chronic back pain at an intensity of ≥4/10 who were randomized to a single-center, double-blind, 12-week, 4-arm, parallel groups controlled clinical trial of (1) low concentration desipramine titrated to reach a serum concentration level of 15 to 65 ng/mL; (2) CBT and active placebo medication (benztropine mesylate, 0.125 mg); (3) low concentration desipramine and CBT; and (4) active benztropine placebo medication. Participants completed the Differential Description Scale and Roland Morris Disability Questionnaires before and after treatment as validated measures of outcomes in back pain intensity and disability, respectively. Participants within each condition showed significant reductions from pre-treatment to post-treatment in pain intensity (mean changes ranged from = −2.58 to 3.87, Cohen's d's = 0.46-0.84) and improvements in pain disability (mean changes = −3.04 to 4.29, Cohen's d's = 0.54-0.88). However, intent-to-treat analyses at post-treatment showed no significant differences between any condition, with small effect sizes ranging from 0.06 to 0.27. The results from this clinical trial did not support the hypothesis that desipramine, CBT, or their combination would be statistically superior to an active medicine placebo for reducing chronic back pain intensity or disability. Key limitations included recruiting 71% of the planned sample size and use of multiple inclusion/exclusion criteria that may limit generalizability to broader populations of patients with chronic back pain. Abstract : A randomized comparison of desipramine, cognitive behavioral therapy, combined therapy, and active placebo showed significant but equivalent improvements for participants with low back pain.